2020
DOI: 10.1016/j.heliyon.2020.e05224
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physiochemical properties and concentration of heavy metals in agricultural soils fertilized with chemical fertilizers

Abstract: The present study aim to assess the effect of phosphate and urea fertilizers on the physicochemical properties, pH and electrical conductivity (EC) of the soil. The effect of these fertilizers on cation exchange capacity (CEC), organic matter (OM), and the possibility of contamination with heavy metals (HM) (Cr, Cu, Cd, Mn, Zn, Ni, Fe, and Pb) were studied on the soils of Alshati agricultural project at different seasons after forty years of fertilization. Uncultivated soil samples were also analyzed for compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 49 publications
3
36
1
3
Order By: Relevance
“…These concerns have triggered assessment efforts of heavy metals in soils in mine waste dumpsites and around the mining areas as a potential first step in mitigating hazards to surrounding ecosystems and human health 4 – 6 . In developing countries such as Zambia, large areas have been affected by past and ongoing mining and smelting of minerals, resulting in chronic exposure to heavy metals by soil, water, plants, animals and humans 7 , 8 . It has been reported that human exposure to excess heavy metals might result in several health disorders, including skin lesions, cardiovascular disease, cancer of different organs, and reproductive defects 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These concerns have triggered assessment efforts of heavy metals in soils in mine waste dumpsites and around the mining areas as a potential first step in mitigating hazards to surrounding ecosystems and human health 4 – 6 . In developing countries such as Zambia, large areas have been affected by past and ongoing mining and smelting of minerals, resulting in chronic exposure to heavy metals by soil, water, plants, animals and humans 7 , 8 . It has been reported that human exposure to excess heavy metals might result in several health disorders, including skin lesions, cardiovascular disease, cancer of different organs, and reproductive defects 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that the physicochemical characteristics of soil mine waste are associated with soil pollution 23 . These physicochemical characteristics determine the impacts of heavy metal pollution on the environment, especially in mining and high-intensity anthropogenic areas 8 . High heavy metal concentrations affect the biodiversity balance and activity of soil organisms, restricting soil organic matter decomposition and nitrogen and phosphorous mineralization 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the relationship between soil pH, C-Organic, and Cation Exchange Capacity (CEC) on the heavy metal content of Pb, Cd, and Hg are explained using ANOVA statistical analysis. A previous study conducted by Salem et al, on the relationship between soil chemistry and heavy metals showed that there was a significant correlation between pH levels, Cation Exchange Capacity (CEC), organic matter content, and electrical conductivity of heavy metals on the land [21]. Also, a study by Cao et al, on the relationship between soil chemical properties and heavy metal content of Pb and Cd in soil and plants (Brissica napus L) using multiple linear regression statistical analysis, showed that the levels of the heavy metals in plants correlated with C-Organic, Cation Exchange Capacity (CEC), availability of Phosphorus (P), availability of Potassium (K), sand and total soil [22].…”
Section: Modelmentioning
confidence: 98%
“…Además, Salem et al (2020) informaron que la aplicación de fertilizantes de fosfato y urea en suelos agrícolas durante cuarenta años de fertilización, proporciona concentraciones considerables de Cr, Cd y Ni, y que las concentraciones de los metales pesados en el suelo varían significativamente con las estaciones (invierno, primavera, verano y otoño). Sin embargo, la aplicación de fertilizantes agrícolas no aumenta significativamente el contenido total de metales pesados en el suelo por encima de los niveles de fondo durante varios años (Rutkowska et al, 2009).…”
Section: Producción De Materia Secaunclassified